Measurement Invariance of the Bergen Social Media Addiction Scale Across Genders - Yue, Heng; Zhang, Xuemin; Cheng, Xiangjuan; Liu, Bo; Bao, Hugejiletu (Frontiers in Psychology, 2022)
Social media addiction has been a hot issue in scientific research during recent years, its antecedents and consequences have been extensively studied. Among these studies, Bergen Social Media Addiction Scale(BSMAS) is one of the most commonly used instruments. However, little is known about whether this scale has the equivalent psychometric properties for men and women. The purpose of the current study is to examine the measurement invariance (including configural invariance, metric invariance, scalar invariance and error variance invariance) of the BSMAS across genders. 1120 participants were recruited from 5 universities. R program was applied to conduct the single-group and multiple-group confirmatory factor analysis(CFA) based on the social media addiction symptom ratings. The results demonstrated that BSMAS was a valid and psychometrically robust instrument for assessing the risk of social media addiction among university students, and that the four types of measurement invariance of the BSMAS across genders were confirmed. Consequently, gender differences of the BSMAS scores are likely to reflect the genuine differences between men and women, and comparisons on the level of social media addiction of university students between gender groups can be meaningfully interpreted.